Curative protection for the satisfaction of the weaker party in contractual relations - Al-Fahham, Hiba Mehdi Adnan; Al-Fetlawy, Ammar Kereem (Journal of Economic, Administrative and Legal Sciences, 2020)
The subject of curative protection to the satisfaction of the weak party in contractual relations is one of the issues that have taken on the opinion of legal jurisprudence, it had to be addressed by research and study, especially in the current situation because of this prominent issue in the relations of people in the field of concluding contracts, despite the importance of this The topic, however, we find that he did not receive a share of the legislative organization commensurate with that importance, because the legislator did not put clear or direct texts through which the weak party’s satisfaction could be protected, but rather different theories scattered in various laws that did not reach the level of familiarity with this issue in all its aspects. Therefore, it is necessary to search for solutions through which we can protect the consent of the weak party ... all that and more that we covered in this study by following both the inductive approach and the comparative approach and the analytical approach, where we extrapolated the most important jurisprudence opinions that were said in this regard, as well as the analysis of legal texts and that Within the scope of Iraqi law and French law, and then we extrapolated the most important doctrinal opinions to the most important results and proposals we have reached to protect the consent of the weak party in contractual relations. The study reached a set of results, among which the researcher reached a set of results, including the creation of the French legislator a new defect in his legislation, which the judiciary had the largest role in alerting to the existence of this defect, its purpose is to protect the consent of the weak party in economic relations, by setting the dependency criterion as the origin of the contractor the weak victim of this kind of coercion. Secondly, the grace period despite thinking is a modern idea, but the French legislator clarified the mechanisms that contractors can follow in their contractual relations and impose a penalty in the event that the weak contracting professional is deprived of it, as it is a right granted to the weak party according to clear and explicit legislative texts. The researcher reached a set of recommendations, among which we recommend the legislator to introduce the defect of economic coercion to address cases of imbalance in the contractual balance that he seeks to achieve in all contractual relationships. We suggest that the Iraqi legislator stipulates the deadline for thinking about its legislation, because the protection that is granted to the weak party is only subsequent protection, at a time when the weak party needs legal protection prior to concluding the contract.
Keywords: therapeutic protection of vulnerable party consent; protection of vulnerable party consent from economic coercion; role of reflection time in protection of vulnerable party consent